Comparative coliform counts of selected beaches in Iloilo City. - Obejuela, Rosemarie S.
This study was conducted to determine the suitability of the selected beaches in Iloilo City for recreational use. The selected sites were the beach boundary of Calumpang and Calaparan, Calaparan and Sto. Niogono Norte, Sto Niogono Norte and Sto. Niogono Sur. Three (3) sampling points from the shoreline to the open sea were designated. The suitability for recreational use was determined through the Standard Total Coliform Count. Among the sampling points of the three sampling areas, only the sampling point 100 of the beach boundary of Calaparan and Sto. Niogono Norte with a coliform count value of 12 MPN per 100 ml met the allowable coliform content of APHA (1989) which is 12 MPN or lower. However, in general, all the sampling areas were not safe for recreational use.